Philosophy, philosophy of sciences and the question of realism (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This paper consists of two main topics: (1) the conception of philosophy as an extremely recursive activity applied to scientific, ethics and educational knowledge; (2) the discussion about realism and the role of the representations in the explanation of cognition (Philosophy of Cognitive Sciences). The validity of the anti-representationism or constructivist-based perspectives, is highlighted in Cognitive Sciences where these pretend to overcome the limitations and prejudices that belong to the previous computacionalism and connectionism perspectives.
Keywords: Philosophic recursivity; constructivism; realism